Changes in the welfare of an injured working farm dog assessed using the Five Domains Model - Littlewood KE; Mellor DJ (Massey University)
© 2016 by the authors; licensee MDPI, Basel, Switzerland.The present structured, systematic and comprehensive welfare evaluation of an injured working farm dog using the Five Domains Model is of interest in its own right. It is also an example for others wanting to apply the Model to welfare evaluations in different species and contexts. Six stages of a fictitious scenario involving the dog are considered: (1) its on-farm circumstances before one hind leg is injured; (2) its entanglement in barbed wire, cutting it free and transporting it to a veterinary clinic; (3) the initial veterinary examination and overnight stay; (4) amputation of the limb and immediate post-operative recovery; (5) its first four weeks after rehoming to a lifestyle block; and (6) its subsequent life as an amputee and pet. Not all features of the scenario represent average-to-good practice; indeed, some have been selected to indicate poor practice. It is shown how the Model can draw attention to areas of animal welfare concern and, importantly, to how welfare enhancement may be impeded or facilitated. Also illustrated is how the welfare implications of a sequence of events can be traced and evaluated, and, in relation to specific situations, how the degrees of welfare compromise and enhancement may be graded. In addition, the choice of a companion animal, contrasting its welfare status as a working dog and pet, and considering its treatment in a veterinary clinical setting, help to highlight various welfare impacts of some practices. By focussing attention on welfare problems, the Model can guide the implementation of remedies, including ways of promoting positive welfare states. Finally, wider applications of the Five Domains Model are noted: by enabling both negative and positive welfare-relevant experiences to be graded, the Model can be applied to quality of life assessments and end-of-life decisions and, with particular regard to negativeexperiences, the Model can also help to strengthen expert witness testimony during prosecutions for serious ill treatment of animals.
Keywords: animal welfare assessment; working dog welfare; leg injury; veterinary evaluation; amputation; rehoming as amputee; negative experiences; positive experiences; quality of life; 0502 Environmental Science and Management; 0608 Zoology; 0702 Animal Production